Surface Velocities of Glaciers in Western Canada from Speckle-Tracking of ALOS PALSAR and RADARSAT-2 data. Issue 1 (2nd January 2018) - Van Wychen, Wesley; Copland, Luke; Jiskoot, Hester; Gray, Laurence; Sharp, Martin; Burgess, David
ABSTRACT: Speckle-tracking of historically acquired ALOS PALSAR and RADARSAT-2 datasets are used to determine the dynamics of major glaciers and ice masses in western Canada over the past decade. For the icefields of the St. Elias Mountains and those that fringe the northern British Columbia/Alaska border, our results are largely consistent with earlier studies that used the same data, but different speckle-tracking techniques, to derive ice motion. However, our results are generally more spatially comprehensive than those previously published, in particular in fast-flowing regions such as Hubbard, Seward, Tweedsmuir and Lowell glaciers. We also produce new velocity maps for the icefields located in the Coast Mountains of southwestern British Columbia and for the Chaba, Clemenceau and Columbia icefields of the Rocky Mountains. Generally, faster flow is present on large ocean- and land-terminating outlet glaciers, particularly those in high accumulation maritime regions. These results, taken together with velocity maps of the Canadian Arctic and Yukon produced in previous studies, mean that baseline maps of glacier velocities determined from speckle tracking of SAR datasets are now available for nearly all the major ice masses of Canada.